TINJAUAN YURIDIS PERIZINAN BERUSAHA PERIKANAN TANGKAP OLEH NELAYAN DI PELABUHAN KARANGANTU - Annisa Nur Aliza; Endang Pandamdari (Reformasi Hukum Trisakti, 2021)
In the capture fisheries business, the government has issued regulations regarding Business Licensing, but in reality many fishing communities still do not comply with these regulations. The formulation of the problem of this research is whether the Business Permit by Fishermen with a Vessel Weight of 1 GT-30 GT at the Karangantu Archipelago Fishing Port is in accordance with the Law on Fisheries and What are the obstacles encountered in Permits for Capture Fisheries at the Karangantu Archipelago Fishing Port and what are the legal settlements. Types of Normative Legal Research, Descriptive Nature of Research, using Secondary research data, Qualitative data analysis, and conclusions drawn using deductive logic. Based on the results of the research, it proved that 10 fishing communities in the Karangantu Archipelago Fishing Port did not comply with the laws and regulations regarding Business Licensing. Obstacles faced not only from the fishermen, namely the lack of understanding of business licensing regulations, besides that from the government there are obstacles, namely still using the old regulations. The advice given is that law enforcement must be enforced in accordance with existing regulations and the government must provide education and counseling to fishing communities regarding business licensinh.